Pemberdayaan Masyarakat Kampung Tua Kota Batam melalui Program Corporae Social Responsibility (CSR) PT. Pertamina Patra Niaga DPPU Hang Nadim - Lestari, Resti (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2022)
Empowerment aims to create community independence, and to achieve the development of a village. This concept of empowerment is then better known as community development (community empowerment). The concept of community empowerment is the offer of a development planning process that relies on the participation and ability of local communities. for this purpose, PT. Pertamina Patra Niaga DPPU Hang Nadim initiate the Kelong Tangguh as an empowerment program for the Kampung Terih fishing group and implementing it in 2021. This program aims to provide additional income for fishermen and provide fishing innovations for the Kampung Terih fishermen group. The Terihindo Jaya Lestari Fishermen Group is a group that carries out empowerment. Seno, from Kampung Terih, is the leader of this group of fishermen, consisting of seventeen men. Mostly, the member of this group is from Malays ethnicity. The discussion about community empowerment programs in Kampung Terih can be analyzed into physical and nonphysical dimensions of empowerment. The implementation of the CSR program in Kampung Terih is the first thing to do by carrying out economic activities such as fish restocking and fish farming using KJA (Floating Net Cages). Meanwhile, the social activities carried out are increasing economic empowerment capacity through group cash. Pemberdayaan bertujuan untuk menciptakan kemandirian masyarakat, sehingga tercapai pembangunan suatu desa. Konsep pemberdayaan ini Kemudian lebih dikenal dengan istilah community development (pemberdayaan masyarakat). Konsep pemberdayaan masyarakat adalah tawaran suatu proses perencanaan pembangunan yang bertumpu pada partisipasi dan kemampuan masyarakat lokal. Program Kelong Tangguh merupakan program pemberdayaan kelompok nelayan Kampung Terih yang dilaksanakan sejak tahun 2021. Program ini bertujuan memberikan tambahan penghasilan bagi nelayan dan memberikan inovasi penangkapan ikan bagi kelompok nelayan Kampung Terih. Kelompok Nelayan Terihindo Jaya Lestari merupakan kelompok yang melakukan pemberdayaan. Kelompok nelayan ini berjumlah sebanyak 17 orang yang di ketuai oleh tokoh masyarakat Kampung Terih yaitu Seno. Kelompok ini terdiri dari nelayan dengan mayoritas suku melayu. Pembahasan mengenai program pemberdayaan masyarakat yang ada di Kampung Terih dapat dianalisa menjadi dimensi pemberdayaan yang fisik dan nonfisik. Penerapan program CSR di Kampung Terih merupakan hal yang baru pertama kali dilakukan dengan melakukan kegiatan ekonomi seperti restocking ikan dan pembudidayaan ikan menggunakan KJA (Keramba Jaring Apung). Sementara kegiatan sosial yang dilakukan adalah peningkatan kapasitas pendayaan ekonomi melalui kas kelompok.